Hubungan antara Status Gizi dan Status Ekonomi dengan Kejadian Menarche - Uliyatul Laili; Fanty A'in Noer Malitasari (STIKes Patria Husada Blitar, 2016)
Menarche is the first menstruation occurs in someone women, and usually occurs at age 11â€“13 years. Incident of menarche in adolescents is influenced by several factors, such as nutritional status, economic, genetic, and environmental. This study aimed to analyze the correlation of nutritional status and economic status with the incidence of menarche. This study used an analytical method with cross sectional prospective design. The sampling used stratified random sampling technique. The independent variable was the nutritional status and economic status, while the dependent variable was the incidence of menarche. The data were analyzed using chi square.The results showed an association between nutritional status and the incidence of menarche with significant value 0.000<ï¡, and also there was a correlation between economic status with the incidence of menarche with significant value 0.002 < ï¡, by significant value it was known that nutritional status was more dominant factor than economic status on the incidence of menarche. Conclusions from this research was getting better nutritional status and economic status possessed child would affect the occurrence of menarche in children.